The impact of logistic performance on intra-ASEAN trade - Ardine, Vedy; Revindo, Mohamad Dian; Rezki, Jahen F.; Dewi, Calista Endrina (Universitas Muhammadiyah Yogyakarta, 2023)
ASEAN has gone a long way in deepening its regional economic cooperation, particularly its trade liberalization. However, ASEAN has comparatively less intraregional trade than the European Union, whose economic integration model they aspire to emulate. As reducing tariffs was no longer an efficient way to increase trade, this study analyzes logistics performance as another factor that may affect trade. Using the gravity model with bilateral trade data from 10 ASEAN member states from 2007 to 2018 with gaps, the results show that the majority of improvements in logistics performance, by both the private sector and government alike, have positive and significant impacts on export value. This finding implies that the collaboration between the private sector and government agencies to improve logistics performance in each ASEAN member state is imperative to foster ASEAN intra-regional trade further.